2021
DOI: 10.1111/bju.15573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SARS‐CoV‐2 virus on male reproductive health

Abstract: The coronavirus 2019 (COVID-19) pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to more than 160 million infections and 3.5 million deaths globally. Men are disproportionately affected by COVID-19, having more severe disease with higher mortality rates than women. Androgens have been implicated as the underlying cause for more severe disease, as the androgen receptor has been noted to upregulate the cell surface receptors that mediate viral cell entry and infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 64 publications
1
49
0
4
Order By: Relevance
“…Direct SARS-CoV-2 infection of Leydig cells may lead to testicular hypofunction, especially in severe diseases. 31 In a postmortem examination of the testes from 12 COVID-19 patients conducted by Yang M, et al, the mean number of Leydig cells per tubule cross-section in COVID-19 testes was significantly lower compared with 5 non-COVID-19 patients' testes (2,2 vs. 7,8; p<0,001). In addition, only 3 out of 12 COVID-19 patients' testes showed normal signs of spermatogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Direct SARS-CoV-2 infection of Leydig cells may lead to testicular hypofunction, especially in severe diseases. 31 In a postmortem examination of the testes from 12 COVID-19 patients conducted by Yang M, et al, the mean number of Leydig cells per tubule cross-section in COVID-19 testes was significantly lower compared with 5 non-COVID-19 patients' testes (2,2 vs. 7,8; p<0,001). In addition, only 3 out of 12 COVID-19 patients' testes showed normal signs of spermatogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Six main targets were classified: receptor tyrosine kinase (RTK), 20S proteasome β5, ion channel, DNA synthesis, antibacteria or protozoa drugs and natural products ( Figure 1 b). Numerous studies report RTK inhibitors, ion channel inhibitors, DNA synthesis inhibitors, antibacteria or protozoa drugs and natural products to be arbovirus antivirals [ 14 , 15 , 16 , 17 ]. However, little work has been conducted regarding 20S proteasome β5 inhibitors as direct-acting antivirals.…”
Section: Resultsmentioning
confidence: 99%
“…Every day, a new study reveals the widespread effects of COVID‐19 on different organs throughout the body. Erectile dysfunction has also been shown to be one of these effects (Kaynar et al, 2022 ; Nassau et al, 2021 ). It has been suggested that the underlying pathophysiological mechanism of ED is endothelial damage.…”
Section: Discussionmentioning
confidence: 99%